Effect of Gender and Age on the Cardiac Enzyme (Creatinine Kinase, CKmm) - Eljamay, Salwa Muftah; Eljamay, Fatma Muftah (Indonesian Journal of Community Services, 2024)
Creatine kinase is expressed at high levels in muscle, where it plays a central role in energy metabolism. Amid to explore the effect of gender and age on baseline blood creatine kinase levels in a large group of adults. Material and Methods: The collected samples 382 from four labs in three Cities in the eastern region of Libya, where 36 samples were collected from the Al-Bara laboratory (83 samples from the Al-Rashid laboratory from the Derna City, 182 samples from the Al-Biruni laboratory in the Tobruk City and 81 samples from the Al-Razi laboratory from Benghazi. Result: The Creatinine Kinase (CK) Result for 382 samples was a high percentage of 215 (56.3 %) and the normal percentage of 167 (43.7 %), the Frequency and percentage of males 196(51.3%), and for females 186(48.7 %), the relationship between age group and the result of Creatinine Kinase (CK) that the highest result was in (51 – 55 years) followed by (41 – 45 years), (61 – 65 years) and > 80, the difference between male and female in the result of Creatinine Kinase (CK) that the number of the highest result was 110 in males, 105 in females, but there are not a huge difference between them, the difference between male and female in the result of Creatinine Kinase (CK) the Correlations between Creatinine Kinase (CK) Result and age, gender due to the p-value more than 0.000. Conclusion: Data analysis shows that age and sex do not affect the result of creatinine cardiac enzymes (CK).